Vacancy cluster in ZnO films grown by pulsed laser deposition - Wang, Zilan; Luo, Caiqin; Anwand, W.; Wagner, A.; Butterling, M.; Rahman, M. Azizar; Phillips, Matthew R.; Ton-That, Cuong; Younas, M.; Su, Shichen; Ling, Francis Chi-Chung (Scientific reports, 2019)
Undoped and Ga-doped ZnO films were grown on c-sapphire using pulsed laser deposition (PLD) at the substrate temperature of 600 °C. Positron annihilation spectroscopy study (PAS) shows that the dominant V Zn -related defect in the as-grown undoped ZnO grown with relative low oxygen pressure P(O 2 ) is a vacancy cluster (most likely a V Zn -nV O complex with n = 2, 3) rather than the isolated V Zn which has a lower formation energy. Annealing these samples at 900 °C induces out-diffusion of Zn from the ZnO film into the sapphire creating the V Zn at the film/sapphire interface, which favors the formation of vacancy cluster containing relatively more V Zn . Increasing the P(O 2 ) during growth also lead to the formation of the vacancy cluster with relatively more V Zn . For Ga-doped ZnO films, the oxygen pressure during growth has significant influence on the electron concentration and the microstructure of the V Zn -related defect. Green luminescence (GL) and yellow luminescence (YL) were identified in the cathodoluminescence study (CL) study, and both emission bands were quenched after hydrogen plasma treatment. The origin of the GL is discussed.